Professional Activity Based on An Integrative Approach Pedagogical-Psychological Diagnostic of Preparation Basics - Mexro’zbek Muxtorjon o’g’li Jo’raboyev; Tursunova Zulxumor Jobir qizi (Academia One Publishing, 2023)
In this article, there is a system of directing students to the profession diagnosing career orientation based on problems, interests and inclinations, his tasks, main directions and mechanisms of its implementation are mentioned. Experience of career orientation by diagnosis of educational activity methods are shown, factors influencing career guidance and ways to eliminate them are provided, as well as suggestions and recommendations system is presented.
Keywords: career guidance; diagnosis; motivational; cognitive